Pengaruh Budaya Organisasi dan Lingkungan Kerja Terhadap Kepuasan Kerja Guru pada SMK Negeri 1 Dumai - Ade Kamelia Putri; Susi Hendriani; Rendra Wasnury (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This research aim to know how influence Organizational Culture variable and Work Environment by simultan and partial to the Employees job satisfaction at SMK Negeri 1 Dumai. In this research use total sampling technic, where all of populations to be a sample used. There are 51 people’s as a sample from the total people’s of populations. This research used primary datas, where are data knows by interview and quistioner. The used analyze in this research is descriptive analyze, and then also used quantitative analyze with the make by SPSS program version 18. From the result examination double linear regresion analyze, which have been simultan test (test F) indicated that Organizational Culture and Work Environment variable have been significant effect to the employees Job Satisfaction. Result of partial test (test T), indicating that Organizational Culture and Work Environment variable have been significant effect to the employees Job Satisfaction. From the double linear regresion make a result is work environment more dominant from Organizational Culture variable to the employees job satisfaction at SMK Negeri 1 Dumai.Keywords: Organizational Culture, Work Environment and Job Satisfaction.